Antioxidant, anti-inflammatory and protective potential of gallic acid against paraquat-induced liver toxicity in male rats - Ali Nouri; Najmeh Salehi-Vanani; Esfandiar Heidarian (Mashhad University of Medical Sciences, 2021)
Objective: As a herbicide, paraquat is a toxic agent that has devastating effects on human health. Gallic acid, on the other hand, is a natural compound that its anti-oxidant values have been reported in previous studies. Given these, this study was designed to evaluate whether gallic acid could reduce the toxic effects of paraquat in the liver of rats.Materials and Methods: Six groups of rats were considered in this study. Group 1 (control group), group 2 (25 mg/kg of paraquat), group 3 (paraquat-plus-silymarin), and groups 4, 5, and 6 (paraquat together with gallic acid at the doses of 25, 50, and 100 mg/kg, respectively). After treatment, biochemical, oxidative, and histopathological parameters were evaluated in the rats.Results: We found that as compared to the control group, while paraquat reduced the hepatic levels of anti-oxidative compounds such as vitamin C (p<0.001), superoxide dismutase (SOD) (p<0.001), and catalase (CAT) (p<0.001), the toxic agent increased the serum levels of protein carbonyl (PC) (p<0.001), malondialdehyde (MDA) (p<0.05), and IL-1β (p<0.001). Paraquat also increased (p<0.05) both serum lipid profile and liver-associated markers in the rats. Nevertheless, gallic acid not only enhanced (p<0.05) the activity of vitamin C, SOD, and CAT but also remarkably reduced (p<0.05) the serum lipid profile, as well as the oxidative and inflammatory markers in the paraquat-treated rats. Gallic acid had also ameliorating effects on the damaged morphology of hepatocytes upon paraquat treatment.Conclusion: The results of this study suggested that gallic acid possesses reinforcing effects on the antioxidant defense system and could be administered to reduce the toxicity of paraquat.